2019
DOI: 10.1111/zph.12564
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Toxoplasma gondii in Crassostrea spp. oysters cultured in an estuarine region in eastern Amazon

Abstract: The aim of the present study was to detect DNA of Toxoplasma gondii in Crassostrea spp. oysters cultured in the state of Pará, Brazil. A total of 400 oysters were directly collected from a fixed rack system. Gills, gastrointestinal tract (GIT) and intervalvular liquid were separated and grouped into pool samples of 10 animals, resulting in 40 samples each of gills, GIT and intervalvular liquid. DNA extraction was performed using a commercial kit, and T. gondii DNA was detected by nested PCR using the primers T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…Studies on bivalve mollusks are relevant in terms of aquatic environment contamination considering that these organisms obtain nutrients from filtration. Some studies have reported a low occurrrence of T. gondii DNA in oysters (Esmerini et al, 2010;Ribeiro et al, 2015;Monteiro et al, 2019;Silva et al, 2020). Monteiro et al (2019) detected T. gondii in oysters from northeastern Pará.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies on bivalve mollusks are relevant in terms of aquatic environment contamination considering that these organisms obtain nutrients from filtration. Some studies have reported a low occurrrence of T. gondii DNA in oysters (Esmerini et al, 2010;Ribeiro et al, 2015;Monteiro et al, 2019;Silva et al, 2020). Monteiro et al (2019) detected T. gondii in oysters from northeastern Pará.…”
Section: Resultsmentioning
confidence: 99%
“…The Norgen® stool extraction kit (Biotek Corp.) and IllustraTM Tissue and Cell Prep Mini Spin kit (GE Healthcare, Little Chalfont, UK) were used to extract DNA from the samples as described by Monteiro et al (2019).…”
Section: Dna Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…felines, can be infected by carnivorism (both mammals and birds), or ingestion of sporulated oocysts. Oocysts can also survive in oysters and mussels retaining its infectivity [ 30 32 ]. Ingestion of non-pasteurized milk or milk products is a potential source of transmission, although not common [ 8 , 33 ].…”
Section: Biological Cycle (Transmission Pathways)mentioning
confidence: 99%